Asking about self-harm and suicide in primary care: Moral and practical dimensions. Issue 4 (April 2021) - Ford, Joseph; Thomas, Felicity; Byng, Richard; McCabe, Rose
Highlights: Questions about self-harm were overwhelmingly framed for a 'no' response. Patients showed difficulty in answering affirmatively. Questions about self-harm and suicide tend to be amalgamated. Thoughts were treated as precursors to action as part of risk assessment. Moralising language is unhelpful if patients are already feeling shame. Abstract: Objective: Self-harm and suicide are important topics to discuss with people experiencing mental health conditions. This study explores how such discussions unfold in practice, and how their moral and practical repercussions manifest for patients and doctors. Methods: Conversation analysis (CA) was used to examine 20 recorded examples of doctors' questions about self-harm and suicide and their ensuing discussions with patients. Results: A tendency to frame questions about self-harm towards a 'no' response, to amalgamate questions around self-harm and suicide, and to limit dialogue around the protective factors offered by family and friends restricted discussion of patients' experiences and concerns. Closed questions about thoughts and actions in the context of risk assessment resulted in missed opportunities to validate distressing thoughts. Patients responding affirmatively often did so in a way that distanced themselves from the negative stigma associated with suicide. Conclusion: The wording of questions, along with negative stigma, can make it difficult for patients to talk about self-harm. Practice implications: Discussions could be improved by asking about self-harm and suicide separately, encouraging discussion when responses are ambiguous and validating distressing thoughts. Negative stigma could be countered by exploring patients' positive reasons for wanting to stay alive.